2008
DOI: 10.1002/eat.20621
|View full text |Cite
|
Sign up to set email alerts
|

Emotional perception in eating disorders

Abstract: The finding of increased fear when exposed to the emotion of anger might be attributed to introversion and conflict avoidance of anorectic patients. No other basic deficiency of emotional perception was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
5
38
2
1
Order By: Relevance
“…The results are in line with the studies and rationale reported by Joos et al (2009);Moritz et al (2011) in the sense that alterations of emotional perception is consonant with the individual's personality characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results are in line with the studies and rationale reported by Joos et al (2009);Moritz et al (2011) in the sense that alterations of emotional perception is consonant with the individual's personality characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…In one study of patients with eating disorders (Joos et al 2009), pictures of the International Affective Picture System (IAPS) were presented to 19 patients with bulimia nervosa, 15 with anorexia nervosa and 25 controls, and participants were asked to observe each image and to report on a scale the emotion they were feeling. The results showed that, when observing aggressive images, the group with anorexia reported feeling more afraid than the other groups, which the authors considered a reflection of those patients' typical avoidance of conflict.…”
Section: Considerations Regarding Alteration Of Perception In Psycholmentioning
confidence: 99%
“…Since these first observations were made, experimental studies of social-cognitive or affective processing in patients with anorexia have produced the identification of different emotional deficits, such as an impairment in prosodic emotional recognition for both negative and positive voices [7,8], a deficit in emotional facial recognition [8,9], a difficulty in the integration of both negative and positive emotional experiences in autobiographical memory [10,11], an increased fear response when confronted with stimuli containing anger [12], and difficulties with emotional recognition of social-affective stimuli [13]. The recent literature review by Oldershaw et al [4] that assesses the emotion processes in patients with anorexia confirms that their socio-emotional functioning is impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in emotional processing are intensely discussed as an important underlying factor or a consequence of disturbed eating behaviour (Joos, Cabrillac, Hartmann, Wirsching, & Zeech, 2009). All of the AN participants in Patching and Lawler's (2009) study described a strong sense of being misunderstood and of not belonging.…”
Section: Connectednessmentioning
confidence: 99%